Jane Eyre and Alexandre Dumas: a previously unknown play. (2nd October 2021) - Stoneman, Patsy; Rahier, François
Abstract : Among the many nineteenth-century stage versions of Jane Eyre, undoubtedly the most influential was The Orphan of Lowood by Charlotte Birch-Pfeiffer. First written in German and performed in Vienna in 1853, this play was translated and performed all over Europe and America, its popularity partly due to its recasting of Rochester as a blameless philanthropic hero. The play generated its own adaptations, and among these is a previously unknown French play by Alexandre Dumas (père), written about 1858 but never performed and assumed lost until 2012. It has now been transcribed and edited by François Rahier as part of a multi-volume edition of Dumas' theatrical works. The material on Dumas in this paper is based on François Rahier's original research, which explains why Dumas' play was not performed and how it was discovered after being thought lost. Comparing the Dumas play with the Birch-Pfeiffer original, and with an 1855 Belgian play which may have been an intermediate source, the paper demonstrates that Dumas greatly expands the Birch-Pfeiffer version, using material drawn directly from Charlotte Brontë's novel, a revision which reverses Birch-Pfeiffer's sanitization of the story. In conclusion, there is some evidence that Charlotte Brontë knew and approved of Dumas' stage works, though she died before his Jane Eyre was drafted.